A Case Report Intravitreal Anti VEGF Bevacizumab on Patient with Hypertension Retinopathy and Exudative Retinal Detachment: Poster Presentation - Case Report - Resident - Sulamanda, Ivan Chandra; Watania, Dyana Theresia (Majalah Oftalmologi Indonesia, 2023)
Introduction : To present a case of intravitreal anti VEGF bevacizumab function on patient with hypertension retinopathy and exudative retinal detachment. Case Illustration : A 29 years old man presented with chief complaint blurry vision with visual acuity 1/60 on both eyes. History of hypertension sinced one year ago and already got hemodialisa treatment twice a week sinced 6 months ago. Ophthalmic examination showed decreased vision on both eyes and posterior segment both eyes we can find macular star and papil edema. Patient had diagnosed with hypertension retinopathy scheie 4 and exudative retinal detachment both eyes. Discussion : Hypertension will cause blood vessels to become damage in the form of sclerosis, thickening of blood vessel walls, and plasma leakage. Hypertension retinopathy acts as predictor of systemic morbidity and mortality due to organ target damage. Regulating systemic disease like blood pressure to become normal will improve clinical signs of hypertension retinopathy. Administration of anti-VEGF intravitreal injection therapy like bevacizumab can improve permeability of blood vessels in retina and decreased volume of exudate in retina. Visual acuity for this patient will improve to become 4/60 for both eyes. Conclusion : Uncontrolled hypertension can lead to organ target damage, which one of that was eyes. Hypertension retinopathy can make complications like exudative retinal detachment if the blood pressure still uncontrolled. Management of exudative retinal detachment caused by hypertension retinopathy was giving intravitreal anti VEGF injection in eyes to repair breakdown of blood retinal barrier, and the blood pressure must be well controlled to maintain permeability of blood retinal barrier.